THE EFFECTS OF HOME LEARNING ENVIRONMENT IN PRESCHOOLER PSYCHOMOTOR DEVELOPMENT - Saliaj, Aurela; Hoxha, Alketa; Zahaj, Majlinda; Nikaj, Sonila; Pura, Bruna (European Scientific Journal, ESJ, 2015)
Background: Several studies have accumulated evidence for the impact of home environment in the preschooler psychomotor development. We wanted to evaluate how the percentages and the relationships of these variables in our country are. Aim of the study: To evaluate how the preschooler’s psychomotor development can be influenced by home learning. Material and methods: This study was conducted in a sample of preschool children in Vlora, Albania. After measuring their psychometric parameters with Age and Stage Questionnaires-3, we evaluated two crucial elements of home learning environment: the quality of child’s room and the book-reading with the parents. In the end of the study we evaluated the associations within these variables. Results: Only 31% of children in this study have a separate well-designed room and 66% of them have shared book-reading with their parents. The odds rate of relationship between room design quality and the level of child psychomotor development is OR=5.2 (P<0.05). The odds rate of relationship between book-reading and the level of child psychomotor development is OR=3 (P<0.05). Conclusions: The level of child psychomotor development is higher when he is raised in a rich stimulating home learning environment. It was children with well-designed rooms (lots of colours and play toys, suitable for their development stage) who have significantly better parameters comparing with other two groups. We found also that children who are stimulated through book-reading are more likely to take high psychomotor scores too.